Comparative Studies on Oils from Some Common Plant Seeds in Nigeria - Akubugwo, I.E.; Chinyere, G.C.; Ugbogu, A.E. (Pakistan Journal of Nutrition, 2008)
Oil were extracted from seeds of the Nigerian plants Pentaclethra macrophylla, Treculia africana, persea gratesima and Telferia occidentalis using n-hexane and their physicochemical properties compared with oils from seed of Cocos nucifera. Percentage oil yield were 20.80, 18.00, 14.00, 18.00 for P. macrophylla. T. africana, P. gratesima and T. occidentalis respectively while the value for C. nucifera seed oil is 32.00. All the five seed oil were odourless and at room temperature liquids. Specific gravity of the seed oils ranged from 0.81-0.90 while peroxide value for all the oil seed were less than 6.00. Saponification values were as low as 106.60 in P. gratesima and as high as 246.00 in C. nucifera seed oils. Iodine values were between 9.60 and 52.40 in the extracts. These results suggest that oil seeds examined may be viable source of oil going by their oil yield. The studied characteristics of all oil extracts in most cases compared favourably with C. nucifera seed oil which is presently used for both domestic and industrial purposes in Nigeria.